RICE PLANTING RITUAL USING MANTRA BY CARUBAN COMMUNITY MADIUN - Dwi Astuti Wahyu Nurhayati (Prasasti: Journal of Linguistics)
Abstract: This study examines local culture especially the use of mantra in planting rice ritual by Javanese in Ngepeh Village Caruban Madiun. The mantra consisted of three parts (early/prototype:Head;Middle/Body; End/wasana: Foot) is used to request the good harvest in which expresses symbolic interaction in the form of salvation.There some factors which influence Javanese community conduct rice planting ritual such as Javanese belief, Javanese worldview, the essence of life. Mantra is used as means to communicate with the Rice Goddess/Dewi Sri and also Danyang of the Village to ask the fertilie harvest and safety from the pest or disasters. It is a case study research which uses a qualitative approach. The technique of collecting the data in this research are participatory observation ( to get the related data to the expression mantra) and In depth Interview (get the the interpretation of the society related to the the essence of life). In conclusion, the relationship of culture and language in the Java community also affects the activity of the use of mantra in the rice planting ceremony (tandur rhyme). In this case the farmer Caruban have inherited the tradition of ancestor worship the rice goddess Dewi Sri as well as The Village Danyang Watcher respected to the next generation and they are considered to whom request that all their wishes can be fulfilled.